A 15-year population-based cohort study of the incidence of Parkinson's disease and dementia with Lewy bodies in an elderly French cohort. Issue 7 (3rd December 2009) - Perez, F; Helmer, C; Dartigues, J F; Auriacombe, S; Tison, F
Abstract : Objective: To provide global and age-related incidence over 65 years of Parkinsonian syndromes (PS), Parkinson's disease (PD) and suspected dementia with Lewy bodies (DLB). Methods: A 15-year prospective population-based elderly cohort study in South-Western France (PAQUID). Results: Incidences found were: 557.7/100 000 person-years for PS, 263 per 100 000 person-years for PD and 112 per 100 000 person-years for suspected DLB. The incidence of all PS, PD and suspected DLB was greater in men. The age-specific incidence of PD decreased over 85, while that of DLB continuously increased, even in the oldest individuals. Conclusions: The authors provide new data on PD and suspected DLB incidence in a large population-based French cohort of subjects aged over 65 and followed up for 15 years. PD incidence decreased in the oldest old contrary to that of suspected DLB cases and Alzheimer's disease.